How Can Intelligent Persona Features Support Online Advertising Work? - Kaate Ilkka; Salminen Joni; Jung Soon-gyo; Olkkonen Rami; Jansen Bernard J. (Italy, 2025)
The concept of “Intelligent Personas” or “AI personas” presented here builds on extant research on datadriven personas and interactive persona systems. With this conceptualization, we particularly focus on outlining a vision for an intelligent end-to-end advertising system that supports human marketers’ decision making by deploying data-driven personas throughout the stages of the online advertising process. We start by defining the relevant concepts, continue by discussing intelligent personas for online advertising, and conclude by proposing research directions that need to be addressed in order to realize the value of personas in such a system, as well as discussing its potential value for the digital marketing profession.
ACHI 2023: The Sixteenth International Conference on Advances in Computer-Human Interactions